Pelatihan Membuat Gantungan Kunci untuk Remaja Sebagai Usaha Baru di Desa Semampir Kecamatan Sedati - Tri Marfiyanto; Dzakiyatul Fuada; Vina Maulidatul Lailiyah (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
Poverty, unemployment, and limited access to education are still social challenges in many parts of Indonesia, including Semampir Village, Sedati District. This beaded keychain making training program is designed as a solution to empower communities, especially teenagers, to improve entrepreneurial skills. This activity aims to equip participants with technical skills in handicraft production as well as basic entrepreneurial knowledge such as digital marketing, product branding, and business management. The results of the training showed an increase in participant motivation and skills in creating high-value products, as well as the growth of a local craftsman community that has the potential to expand the market online. This program is expected to create independent business opportunities, reduce unemployment rates, and strengthen the village economy in a sustainable manner.